Les effets des équipements hydroélectriques en Amazonie - Céline Broggio; Martine Droulers (EchoGéo)
This paper deals with the medium- and long-term effects of dams and hydroelectric plants installed since the 1980s in the Brazilian Amazon on the reorganization of the surrounding territories. Hydroelectric installations are an aspect of the Amazonian pioneer frontier. Due to the major disruptions caused by their installation, a process of territorial resilience takes place in a post-frontier context. Can the analysis of the case of the Tucurui dam (State of Para), with thirty years of retrospective, give some insight on the current situation in the region of Porto Velho (State of Rondonia) where two large hydroelectric plants (Santo Antônio and Jirau) were installed in the late 2000s?